A Class of Metric Spaces Which Do Not Coarsely Contain Expanders (Communications in Mathematical Research, 2021)
In this paper, a class of metric spaces which include Hilbert spaces andHadamard manifolds are defined. And the expanders cannot be coarsely embeddedinto this class of metric spaces are proved.
Keywords: coarse embedding; expander; special metric space.